Construction of Intensity-Duration-Frequency Curves for Precipitation with Annual Maxima Data in Kumulur Region - S., Vanitha; Ravikumar, V. (International Journal of Bio-resource and Stress Management, 2017)
Intensity–duration–frequency (IDF) relationship of rainfall amounts is one of the most commonly used tools in water resources engineering for planning, design and operation of water resources projects. The Intensity-Duration-Frequency relationship is a mathematical relationship between the rainfall intensity, duration and return period. This relationship is determined through statistical analysis of recorded rainfall data. The objective of this study is to derive IDF relationship of rainfall at Kumulur region. A total durations ranging from 10 minutes to 24 hr (10 min, 20 min, 30 min, 60 min, 120 min, 180 min, 360 min, 720 min and 1440 min) for return periods of 2, 5, 10, 25, 50 and 100 years were analyzed. In this study, Yearly maximum rainfall data for Kumulur (1991–2014) was used. Empirical reduction formula of Indian Meteorological Department (IMD) has been used to estimate the short duration rainfall intensity from yearly maximum rainfall data. Gumbel and Log Pearson Type III (LPT III) Distribution method was used to construct IDF curves and equations. The results obtained using Gumbel method is somewhat higher than the outcomes obtained using the LPT III distribution method. The chi-square goodness of fit test was used to determine the best fit probability distribution. This study will be helpful in many design problems related to watershed management, such as runoff disposal and erosion control, it is necessary to know the rainfall intensities of different durations and different return periods.